CREATING A HEALTHY SCHOOL ENVIRONMENT: POLICIES AND BEST PRACTICES - Rina Wijayanti; Romadhon; Melyana R Pugu; Al-Amin (Jurnal Kesehatan, 2024)
Creating a healthy school environment is an important aspect of developing students' learning capacity and well-being. Various studies have explored the implementation of policies and best practices that support physical, mental and social health in the school environment. The research method used was literature research. The results show that hygiene standards, air quality, nutrition, physical activity, comprehensive health education and emotional support are key factors in creating healthy schools. The multidisciplinary involvement of educators, parents, and health practitioners showed significant improvement in the successful implementation of this policy. In addition, anti-bullying and mental health promotion practices have contributed to a decrease in school violence cases and an increase in students' mental awareness.